2021
DOI: 10.1002/mde.3388
|View full text |Cite
|
Sign up to set email alerts
|

Academic directors in board and corporate expropriation: Evidence from China

Abstract: Previous studies have recognized that the presence of academic directors on the board leads to better corporate governance and accounting quality. However, studies have yet to establish the effectiveness of academic directors in mitigating corporate expropriation in emerging markets. The purpose of this study is to investigate the effect of academic directors on corporate expropriation in Chinese listed firms. It is observed that the presence of the academic director in the board mitigates earnings management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 85 publications
0
10
0
3
Order By: Relevance
“…Reputed directors enhances the overall value of firm (Okpamen and Ogbeide, 2020). The previous studies on the directors having academic position have shown that they curtail the managerial expropriations (Khan et al, 2022) and enhance the corporate philanthropy (Cho et al, 2017). Academics can collaborate with different stakeholders and act as catalyst in an organization networking, both internal and external.…”
Section: F7mentioning
confidence: 99%
See 1 more Smart Citation
“…Reputed directors enhances the overall value of firm (Okpamen and Ogbeide, 2020). The previous studies on the directors having academic position have shown that they curtail the managerial expropriations (Khan et al, 2022) and enhance the corporate philanthropy (Cho et al, 2017). Academics can collaborate with different stakeholders and act as catalyst in an organization networking, both internal and external.…”
Section: F7mentioning
confidence: 99%
“…Literature has identified the role of academics in corporate policies (Wang, 2020;Huang and Teklay, 2021;Khan et al, 2022). We propose that the independent academic directors can enhance the CID based on upper echelons theory.…”
Section: Independent Directorsmentioning
confidence: 99%
“…State ownership can leverage the advantages of human resources and other resources (Zhu et al, 2005). Khan et al (2022) observed that the presence of the academic director on the board mitigates earnings management and abnormal investments and enhances dividend payments and the critical mass of academic directors curbs the expropriator managerial behavior of Chinese listed firms. Liu, Wang, and Zhu (2021) thought the education level of the CEO was positively related to platform survival probability, but the effects of the CEO's education and experience were less significant for state‐owned platforms.…”
Section: Evolution Of Opinions On the Soermentioning
confidence: 99%
“… Khan et al (2022). observed that the presence of the academic director on the board mitigates earnings…”
mentioning
confidence: 99%
“…Yet, while a chief executive officer (CEO) is hired to improve management efficiency, various agency problems may arise as a result of the conflict of interests between the manager's self‐interests and those of the shareholders who are concerned with enhancing firm value (Abdoh & Liu, 2021; Chen et al, 2022; Jensen & Meckling, 1976). In order to mitigate the agency conflicts between managers and shareholders, prior researchers have provided a number of control mechanisms, such as supervision by external shareholders (e.g., Ali & Zhang, 2015; Demsetz & Lehn, 1985), supervision by the board of directors (e.g., Ding et al, 2010; Khan et al, 2022), and managerial compensation plans (e.g., Bettis et al, 2018; Huang et al, 2022; Lin et al, 2012). Prior researches have evidenced that there exists an explicitly linkage between managerial compensation and various performance measure indexes (e.g., Canace et al, 2022).…”
Section: Introductionmentioning
confidence: 99%